The Influence Of Tax Fairness, Ethical Attitudes And Commitment On Taxpayer Compliance Behavior - Siahaan, Fadjar O.P. (Accounting Department,, 2005)
The aim of this study is to examine the direct and indirect effect of tax faimess, ethical attitudes and commitment on taxpayer compliance behavior. This study was conducted in Surabaya, East Java. The respondents of the study are individual taxpayer working in service industries. Eighty six taxpayers participated in this study. The ï¬ndings of this study show that: (1) the direct effect tax faimess on taxpayer compliance behavior is positive and signiï¬cant (2) the indirect effect of tax faimess on taxpayer compliance behavior through ethical attitudes is positive and signiï¬cant (3) the indirect effect of tax faimess on taxpayer compliance behavior through commitment is positive and signiï¬cant. This study contribute not only to the research literature but also to help govemment to develop strategies toward improving compliance. Keywords: tax faimess, ethical attitudes, commitment, taxpayer compliance behavior.